2001
DOI: 10.1007/s002100000351
|View full text |Cite
|
Sign up to set email alerts
|

H 3 receptor-mediated inhibition of intestinal acetylcholine release: pharmacological characterization of signal transduction pathways

Abstract: The present study investigates the mechanisms through which prejunctional histamine H3 receptors modulate intestinal cholinergic neurotransmission. The experiments were performed on longitudinal muscle-myenteric plexus preparations of guinea pig ileum, preincubated with [3H]choline, superfused with physiological salt solution containing hemicholinium-3, and subjected to electrical field stimulation. The stimulation-induced outflow of radioactivity was taken as an index of endogenous acetylcholine release. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Millimolar concentrations of histamine can be reached in inflammatory districts4546 and probably in the gastrointestinal tract after ingestion of histamine rich-foods or foods triggering histamine release from the body. Although interactions between histamine and Ach have been already described both at peripheral and central levels474849, findings of the present study may offer a novel point of view for the comprehension of the complex relationship between histaminergic and cholinergic systems. Noteworthy, while histamine metabolism leads to the loss of its biological activity, it does not alter the catalytic potential of its imidazole ring, at least until the complete removal from the internal milieu or the cell cytoplasm.…”
Section: Discussionmentioning
confidence: 77%
“…Millimolar concentrations of histamine can be reached in inflammatory districts4546 and probably in the gastrointestinal tract after ingestion of histamine rich-foods or foods triggering histamine release from the body. Although interactions between histamine and Ach have been already described both at peripheral and central levels474849, findings of the present study may offer a novel point of view for the comprehension of the complex relationship between histaminergic and cholinergic systems. Noteworthy, while histamine metabolism leads to the loss of its biological activity, it does not alter the catalytic potential of its imidazole ring, at least until the complete removal from the internal milieu or the cell cytoplasm.…”
Section: Discussionmentioning
confidence: 77%
“…The same group reported the synthesis of selective ligands for H 3 R, including the agonist (R)-α-methylhistamine and the antagonist thioperamide [44] . Using selective H 3 R agonists and antagonists it was shown that signal transduction by the H 3 R is mediated by pertussis toxin-sensitive G i /G o proteins leading to a decrease in intracellular cAMP concentrations [45,46] and to a decrease in extracellular Ca 2+ influx in neurons [47] .…”
Section: Histamine In the Brainmentioning
confidence: 99%
“…Schlicker et al (1994) indicated that H 3 receptormediated inhibition of noradrenaline release was dependent of Ca 2ϩ influx. Also, Blandizzi et al (2001) suggested that H 3 receptor-inhibition of intestinal acetylcholine release could be mediated by modulation of N-type calcium channels. A direct coupling of G protein ␤␥ complexes to Ca 2ϩ channels might produce these effects of H 3 receptors on voltage-dependent calcium channels (Diverse-Pierluissi et al, 1997 and 2000).…”
Section: Discussionmentioning
confidence: 99%